Zirconium oxide composite sintered body and method for producing same

By adding ZrO2, HfO2, Nb2O5, Ta2O5, Group I elements and TiO2 to the zirconia composite sintered body, the problem of insufficient strength and machining properties of zirconia sintered body in dental applications is solved, and efficient dental treatment and Tool efficiency.

CN119325459APending Publication Date: 2025-01-17KURARAY NORITAKE DENTAL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380044114.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-06-01
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

In dental applications, zirconia sintered bodies have insufficient strength and machining, resulting in long treatment time, large tools consumption, and difficulty in large-scale machining in sintered state, which affects the treatment efficiency and economy.

Method used

By adding ZrO2, HfO2, Nb2O5 and/or Ta2O5 to the zirconia composite sintered body, and including Group I elements and TiO2, to suppress phase transition and improve mechanical processing properties, and to form a sintered body with high intensity and light transmittance.

Benefits of technology

Rapid mechanical processing in the sintered state is achieved, reducing tool consumption, improving productivity and economicality of dental patches, and shortening treatment time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161823160000281
    Figure BDA0005161823160000281
  • Figure BDA0005161823160000291
    Figure BDA0005161823160000291
  • Figure BDA0005161823160000301
    Figure BDA0005161823160000301
Patent Text Reader

Abstract

Provided is a zirconia composite sintered body which has strength and light transmittance suitable for dental use, and which has excellent machinability. The present invention pertains to a zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of suppressing phase change of zirconia, and Nb2O5 and / or Ta2O5, the total content of ZrO2 and HfO2 being 78-97.5 mol%, the content of the stabilizer being 1-12 mol%, the total content of Nb2O5 and Ta2O5 being 1-9 mol%, and the total content of Nb2O5 and Ta2O5 being 1-9 mol% per 100 mol% of the total of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5. The zirconia composite sintered body further comprises a group I element and TiO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a zirconia composite sintered body and a method for producing the same. More specifically, the present invention relates to a zirconia composite sintered body having excellent strength and light transmittance and excellent processability in a sintered body state and a method for producing the same. Background Art

[0002] Ceramics made of metal oxides are widely used in industry. Among them, sintered zirconium oxide is used for dental materials such as dental prostheses due to its high strength and aesthetic properties.

[0003] Since zirconia sintered bodies are excellent in strength, they are unlikely to break when used for dental materials such as prostheses. In addition, since zirconia sintered bodies are highly translucent, they are difficult to stain in the oral cavity, so they are also excellent in aesthetics. On the other hand, after being made into a sintered body in a completely sintered state, they are almost impossible to process using a dental processing machine because of their high hardness. For example, if a zirconia sintered body having a cubic shape is machined in order to obtain a zirconia sintered body having a shape consistent with the shape of the patient's teeth, the consumption of metal processing tools becomes very large, and a lot of time is required to manufacture only one dental prosthesis.

[0004] Based on such circumstances, when a zirconia sintered body is used as a dental material, it is usually not a completely sintered sintered body, but a pre-sintered body in a semi-sintered state that is easy to process is processed into the shape of a desired dental prosthesis, and then further sintered to produce a sintered body processed into the shape of a target dental prosthesis. Thereafter, the sintered body is subjected to a slight adjustment process so that the sintered body having the shape of a dental prosthesis is suitable and does not feel incompatible when it is installed in the oral cavity of a patient in a dental hospital.

[0005] In recent years, when processing a calcined body into a desired shape of a dental prosthesis, machining based on a CAD / CAM system is used to obtain a shape that matches the tooth of the patient's treatment site, and calcined bodies (polished blanks) for CAD / CAM systems are often used.

[0006] As described above, when zirconia sintered bodies are used for dental material applications, due to the unique problems in sintering zirconia, large-scale machining is avoided after the sintered bodies are made, and the processing of the sintered bodies is limited to the level of fine adjustment when they are installed in the patient's mouth in a dental clinic. In other words, the use of dental materials is handled based on the staged physical property changes caused by the sintering of zirconia.

[0007] Furthermore, in dental treatment, in consideration of the unique conditions caused by the physical properties of the above-mentioned zirconia sintered body, treatment is generally performed through the following multiple steps: a step of obtaining information on the shape of the patient's oral cavity, such as dentition information; a step of machining a calcined body (grinded blank) into the shape of a desired dental prosthesis by a CAD / CAM system based on the acquired information; a step of sintering the calcined body having the shape of the desired dental prosthesis to obtain a sintered body; and a step of performing minute adjustment processing on the sintered body in a manner that is appropriate and does not feel incompatible when installed in the patient's oral cavity in a dental hospital.

[0008] Thus, in dental treatment using a dental prosthesis made of sintered zirconium oxide, it is difficult to complete all the above steps in one visit to the hospital. Therefore, in many cases, even if it is just one tooth, multiple visits to the dental hospital are required, and the treatment period from the start to the end of the treatment often takes more than one month.

[0009] On the other hand, patients want to reduce the number of visits to the hospital and complete treatment in a short period of time in order to shorten the time until new artificial teeth are installed after treatment and reduce the burden of going to the hospital.

[0010] Assuming that the zirconia sintered body can be extensively machined, there is no need to temporarily machine the pre-burned body and then manufacture the sintered body by sintering. After obtaining information about the shape of the patient's oral cavity, the unprocessed sintered body can be machined into the shape of the desired dental prosthesis through a CAD / CAM system based on the information, installed in the patient's mouth and fine-tuned, so that dental treatment can be completed in one day.

[0011] In addition, when using dental prostheses, it is possible to complete dental treatment in one day when using materials other than zirconia, such as lithium disilicate glass ceramics and feldspar glass ceramics. However, in the case of zirconia sintered bodies, there are unique circumstances caused by the physical properties of zirconia sintered bodies, making it difficult to achieve.

[0012] As described above, since the demand for zirconium oxide is high from the perspectives of strength and aesthetics, along with the increasing demand for shortening the treatment period, a zirconium oxide sintered body has been proposed which has excellent machinability in the sintered body state and can be processed from a prismatic or disc-shaped ground blank into the shape of a desired dental prosthesis (for example, Patent Documents 1 and 2).

[0013] For example, Patent Document 1 discloses a machinable zirconia and a method for manufacturing the same, wherein the machinable zirconia is a sintered body formed in a manner comprising a tetragonal zirconia composite powder and a TiO2 nanopowder having a mass ratio greater than 0 mass % and less than 2.5 mass % relative to the zirconia composite powder, wherein the tetragonal zirconia composite powder contains 79.8 to 92 mol % of ZrO2 and 4.5 to 10.2 mol % of Y2O3, and 3.5 to 7.5 mol % of Nb2O5 or 5.5 to 10.0 mol % of Ta2O5.

[0014] In addition, Patent Document 2 discloses a machinable zirconium oxide composition and a method for manufacturing the same using a raw material, wherein the raw material contains 78 to 95 mol % of ZrO2, 2.5 to 10 mol % of Y2O3, and 2 to 8 mol % of Nb2O5 and / or 3 to 10 mol % of Ta2O5, and the main crystalline phase of ZrO2 is monoclinic.

[0015] Prior art literature

[0016] Patent Literature

[0017] Patent Document 1: Japanese Patent Application Publication No. 2015-127294

[0018] Patent Document 2: International Publication No. 2021 / 132644 Summary of the invention

[0019] Problems to be solved by the invention

[0020] The zirconia sintered bodies disclosed in Patent Documents 1 and 2 can be machined even in a sintered state. However, the processing time for cutting out dental prostheses is prolonged, and there is room for improvement from the viewpoint of shortening treatment time.

[0021] In addition, although the zirconia sintered bodies disclosed in Patent Documents 1 and 2 can be machined, the number of dental prostheses obtained by continuous processing using one processing tool is small and the processing tool is consumed quickly. Therefore, there is a problem that the frequency of replacing the processing tool increases, the tool replacement time increases, and the productivity and economic efficiency decrease.

[0022] Furthermore, if the hardness of the material is reduced in order to improve machinability, there is a problem that the strength of the material is reduced.

[0023] An object of the present invention is to provide a zirconia composite sintered body having strength and light transmittance suitable for dental use and excellent machinability.

[0024] Solutions to Solve Problems

[0025] In order to solve the above-mentioned problems, the present inventors conducted in-depth research and found that the problems can be solved by further including Group I elements and TiO2 in a zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and / or Ta2O5 in a specified proportion. Based on this insight, further research was carried out to complete the present invention.

[0026] That is, the present invention includes the following inventions.

[0027] [1] A zirconia composite sintered body comprising ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconia, and Nb2O5 and / or Ta2O5,

[0028] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,

[0029] The total content of ZrO2 and HfO2 is 78-97.5 mol%.

[0030] The content of the stabilizer is 1 to 12 mol%.

[0031] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.

[0032] The zirconia composite sintered body further comprises a Group I element and TiO2.

[0033] [2] The zirconium oxide composite sintered body according to [1], wherein the content of TiO2 is greater than 0 mass% and less than 5.0 mass% relative to 100 mass% of the total of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5.

[0034] [3] A zirconia composite sintered body according to [1] or [2], wherein the content of the aforementioned Group I element is greater than 0 mol% and less than 3 mol% relative to the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5.

[0035] [4] The zirconium oxide composite sintered body according to any one of [1] to [3], wherein the Group I element includes at least one element selected from the group consisting of Li, Na and K.

[0036] [5] The zirconium oxide composite sintered body according to any one of [1] to [4], wherein when the content of the stabilizer is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.

[0037] [6] The zirconium oxide composite sintered body according to any one of [1] to [5], wherein the stabilizer contains Y2O3 and / or CeO2.

[0038] [7] The zirconium oxide composite sintered body according to any one of [1] to [6], wherein the content of TiO2 is 0.6 mass % or more and 4.3 mass % or less.

[0039] [8] The zirconia composite sintered body according to any one of [1] to [7], wherein the biaxial bending strength measured in accordance with ISO 6872:2015 is 350 MPa or more.

[0040] [9] The zirconia composite sintered body according to any one of [1] to [8], wherein the average grain size of the zirconia composite sintered body is 0.5 to 5.0 μm.

[0041]

[10] The method for producing a zirconia composite sintered body according to [1] comprises:

[0042] A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5,

[0043] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,

[0044] The total content of ZrO2 and HfO2 is 78-97.5 mol%.

[0045] The content of the stabilizer is 1 to 12 mol%.

[0046] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.

[0047] The raw material composition further comprises a raw material compound of a Group I element and TiO2; and

[0048] A step of sintering the molded body.

[0049]

[11] The method for producing a zirconia composite sintered body according to

[10] , wherein the raw material compound of the Group I element is a hydroxide and / or a salt of the Group I element.

[0050] The method for producing a zirconium oxide composite sintered body further includes a step of wet-mixing the respective raw materials of the raw material composition in a solvent containing water to obtain the raw material composition.

[0051]

[12] The method for producing a zirconium oxide composite sintered body according to

[10] or

[11] , wherein in the raw material composition, the stabilizer includes a stabilizer that is insoluble in ZrO 2 and HfO 2 .

[0052]

[13] The method for producing a zirconia composite sintered body according to any one of

[10] to

[12] , wherein the step of sintering the molded body comprises:

[0053] The sintering process is performed at 1300-1680°C, and

[0054] A process of performing HIP treatment at 1200°C or above.

[0055]

[14] The method for producing a zirconia composite sintered body according to

[13] , comprising, after the HIP treatment step, a step of performing a heat treatment at 1400° C. or less in the air or in an oxygen-excess atmosphere.

[0056] Effects of the Invention

[0057] According to the present invention, it is possible to provide a zirconia composite sintered body which has strength and light transmittance suitable for dental use and is excellent in machinability.

[0058] In addition, according to the present invention, a zirconia composite sintered body can be provided, which can be machined in the state of a sintered body, and the machining time is short based on the machining, and the consumption of machining tools can be suppressed. A large number of dental restorations can be cut out through continuous processing using one machining tool (hereinafter also referred to as "continuous processing"), and the productivity and economy are excellent. DETAILED DESCRIPTION

[0059] The zirconia composite sintered body of the present invention comprises ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia (hereinafter also referred to as "stabilizer"), and Nb2O5 and / or Ta2O5.

[0060] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,

[0061] The total content of ZrO2 and HfO2 is 78-97.5 mol%.

[0062] The content of the stabilizer is 1 to 12 mol%.

[0063] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.

[0064] The zirconia composite sintered body further comprises a Group I element and TiO2.

[0065] The zirconia composite sintered body of the present invention refers to a state (sintered state) in which ZrO2 particles (powder) are completely sintered. It should be noted that in this specification, the upper limit and lower limit of the numerical range (the content of each component, the ratio calculated from each component, the value and each physical property, etc.) can be appropriately combined. In this specification, machining includes cutting and grinding. In addition, machining can be any of wet machining and dry machining, without special limitation.

[0066] In the present specification, the content of each component in the zirconia composite sintered body can be calculated from the amount of raw materials charged.

[0067] In addition, the content of each component of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 in the zirconia composite sintered body can also be measured by, for example, inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis, etc.

[0068] The content rate (mol%) of the Group I element is the external addition rate relative to the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5. Therefore, the content rate of the Group I element in the zirconia composite sintered body can be calculated by converting the added amount (mass) of the raw materials at the time of addition into mol%.

[0069] In addition, the content rate (mass %) of TiO2 is the external addition rate relative to the total of 100 mass % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5. Therefore, the content rate of TiO2 in the zirconia composite sintered body can be calculated from the amount (mass) of raw materials added during addition.

[0070] The reason why the zirconia composite sintered body of the present invention has strength and light transmittance suitable for dental use and has high machinability and can be machined in a sintered state is not yet clear, but is presumed as follows.

[0071] It can be speculated that in the zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and / or Ta2O5, the presence of Group I elements at the grain boundaries of the zirconia particles causes the Group I elements to act in a direction of reducing the grain boundary strength and facilitating the peeling between the particles, thereby facilitating cutting and improving machinability.

[0072] It can be speculated that in the zirconia composite sintered body containing ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, and Nb2O5 and / or Ta2O5, the presence of Group I elements at the grain boundaries of the zirconia particles (hereinafter also referred to as "grain boundaries") causes the Group I elements to act in a direction of reducing the grain boundary strength and facilitating peeling between particles, thereby facilitating cutting and improving machinability.

[0073] In addition, since Nb2O5 and / or Ta2O5 act in the direction of coarsening the microstructure and reducing the hardness in the zirconia composite sintered body, the Group I element and Nb2O5 and / or Ta2O5 are integrated to act in the direction of improving the machinability. Therefore, it is estimated that the Group I element and Nb2O5 and / or Ta2O5 act as a whole, have the strength required as an artificial tooth, and can provide excellent machinability, so in addition to shortening the processing time based on mechanical processing, it is also possible to suppress the consumption of processing tools, increase the number of dental prostheses obtained by continuous processing using one processing tool, and solve the unique problems in the continuous processing of sintered bodies.

[0074] It is speculated that the zirconium oxide composite sintered body of the present invention has the following structure, which includes: zirconium oxide particles containing ZrO2, HfO2, and a stabilizer capable of inhibiting the phase transformation of zirconium oxide; an adhesive component containing ZrO2, HfO2, Nb2O5 and / or Ta2O5, and TiO2; and a stripping component containing a Group I element.

[0075] TiO2 mainly exists in the grain boundary together with the Group I elements. By making TiO2 exist locally in various places of the grain boundary, the grain boundary strength weakened by the presence of the Group I elements can be unevenly produced as shown in the dotted line, thereby suppressing the reduction of the aforementioned effect obtained by the Group I elements and Nb2O5 and / or Ta2O5 becoming one, and the grain boundary strength can be improved. Furthermore, in the presence of Nb2O5 and / or Ta2O5, TiO2 can improve translucency. Therefore, according to the present invention, it is inferred that a zirconia composite sintered body with strength and translucency suitable for dental use and high machinability can be obtained.

[0076] In the zirconia composite sintered body of the present invention, the Group I element functions as a free-machining agent as described above, and further, the strength and light transmittance are not impaired.

[0077] In certain suitable embodiments, the content of the Group I element contained in the zirconia composite sintered body of the present invention is preferably greater than 0 mol% and less than 3 mol%. From the viewpoint of better machinability and further increasing the number of dental restorations that can be continuously processed with one processing tool, it is more preferably from 0.05 mol% to 3 mol%. From the viewpoint of better strength, it is further preferably from 0.06 mol% to 2.5 mol%, particularly preferably from 0.07 mol% to 1.0 mol%, and most preferably from 0.08 mol% to 0.34 mol%.

[0078] Any element of Group I can be used as long as the above-mentioned content is used.

[0079] On the other hand, Na, K, Rb, Cs and Fr have higher atomic weights than Li. As the atomic weight increases, the force acting in the direction that easily causes the particles to peel off each other increases, and the content required to achieve the effect of the present invention tends to decrease. Therefore, the above-mentioned content is particularly suitable when the Group I elements are K, Rb, Cs and Fr.

[0080] In certain other suitable embodiments, the content of the Group I element contained in the zirconia composite sintered body of the present invention is preferably greater than 0 mol% and less than 4.2 mol%. From the viewpoint of better machinability and further increasing the number of dental restorations that can be continuously processed with one processing tool, it is more preferably from 0.05 mol% to 4.0 mol%, further preferably from 0.06 mol% to 3.8 mol%, particularly preferably from 0.07 mol% to 3.6 mol%, and most preferably from 0.08 mol% to 3.5 mol%.

[0081] Any element of Group I can be used in the above-mentioned content.

[0082] For example, when the Group I element is Li and / or Na, the content of the Group I element contained in the zirconia composite sintered body of the present invention may be the above-mentioned content.

[0083] The content of the Group I element in any embodiment may be appropriately used as long as the effects of the present invention can be obtained in consideration of the contents of other components and the like.

[0084] In another suitable embodiment, the content of the Group I element contained in the zirconia composite sintered body of the present invention may be greater than 3 mol % and 4.2 mol % or less as long as the effects of the present invention are achieved.

[0085] Examples of the Group I element include Li, Na, K, Rb, Cs, and Fr. The Group I element may be used alone or in combination of two or more.

[0086] As some embodiments, a zirconia composite sintered body may be provided, wherein the Group I element includes one element selected from the group consisting of Li, Na, and K.

[0087] In the zirconium oxide composite sintered body of the present invention, the total content of ZrO2 and HfO2 is 78 to 97.5 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5. From the viewpoint of better light transmittance and strength, it is preferably greater than 79 mol% and less than 96 mol%, more preferably greater than 80 mol% and less than 94 mol%, and further preferably greater than 81 mol% and less than 93 mol%.

[0088] Examples of stabilizers that can inhibit the phase transition of zirconium oxide include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), lanthanum oxide (La2O3), erbium oxide (Er2O3), praseodymium oxide (Pr2O3, Pr6O3), and vanadium oxide (Pr2O3). 11 ), samarium oxide (Sm2O3), europium oxide (Eu2O3), thulium oxide (Tm2O3), gallium oxide (Ga2O3), indium oxide (In2O3) and ytterbium oxide (Yb2O3), and Y2O3 (yttrium oxide) and / or CeO2 are preferred from the viewpoint of better effects of the present invention, especially excellent aesthetics. The aforementioned stabilizer may be used alone or in combination of two or more.

[0089] As described above, the Group I element works together with Nb2O5 and / or Ta2O5, and these components and TiO2 will not impair the effect of the aforementioned stabilizer. Therefore, the aforementioned stabilizer is not particularly limited and achieves the effect of the present invention.

[0090] In the zirconia composite sintered body of the present invention, the content of the stabilizer capable of inhibiting the phase transformation of zirconia is 1 to 12 mol% in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5 and Ta2O5, preferably 2 mol% or more and 10 mol% or less, more preferably 3 mol% or more and 8 mol% or less, and further preferably 3.5 mol% or more and 7.5 mol% or less in terms of better light transmittance and strength. When the content of the aforementioned stabilizer exceeds 12 mol%, it is difficult to obtain sufficient machinability.

[0091] Some suitable embodiments include a zirconia composite sintered body, wherein the stabilizer capable of suppressing the phase transformation of zirconia includes Y2O3 and / or CeO2, and the total content of Y2O3 and CeO2 is 2 mol% or more and 10 mol% or less.

[0092] As some other suitable embodiments, there can be mentioned a zirconia composite sintered body, in which the stabilizer capable of suppressing the phase transformation of zirconia includes Y 2 O 3 , and the content of Y 2 O 3 is 2 mol % or more and 10 mol % or less.

[0093] In any of the above-mentioned embodiments, the contents of Y2O3 and CeO2 may be appropriately changed within the range described in this specification. For example, from the perspective of better light transmittance and strength, the combined content of Y2O3 and CeO2 may be greater than 2.5 mol % and less than 10 mol %, or may be greater than 3 mol % and less than 9 mol %.

[0094] In the zirconia composite sintered body of the present invention, the total content of Nb2O5 and Ta2O5 is 1 to 9 mol% in the total of 100 mol% of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5, preferably 1.5 mol% or more and 8.5 mol% or less. From the perspective of functioning in an integrated manner with the Group I elements and having better machinability, it is more preferably 2.5 mol% or more and 8 mol% or less, and further preferably 3 mol% or more and 7 mol% or less. When the total content of Nb2O5 and Ta2O5 is less than 1 mol%, it is difficult to obtain sufficient machinability. In addition, when the total content of Nb2O5 and Ta2O5 exceeds 9 mol%, the resulting zirconia composite sintered body will have defects, etc., and it is difficult to obtain sufficient physical properties.

[0095] As described above, Nb2O5 and Ta2O5 act in the direction of coarsening the fine structure and reducing the hardness, and work as a whole with the Group I elements to impart excellent machinability. In addition, through the interaction with other components added to the zirconia composite sintered body (such as TiO2, Al2O3) and the application of HIP, the sintering density can be maximized to ensure the aesthetics of natural teeth.

[0096] The content of each component of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 is a ratio when the total of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 is 100 mol%, and the total of ZrO2, HfO2, stabilizer, Nb2O5 and Ta2O5 does not exceed 100 mol%. For example, when the raw material composition contains Nb2O5 and does not contain Ta2O5, the content of each component of ZrO2, HfO2, stabilizer and Nb2O5 refers to the content ratio relative to the total of ZrO2, HfO2, stabilizer and Nb2O5, which is 100 mol%.

[0097] In addition, when the content of the stabilizer is set to A mol% and the total content of Nb2O5 and Ta2O5 is set to B mol%, from the viewpoint of machinability, the ratio of A / B is preferably 0.9 to 3, more preferably 0.95 to 2, and further preferably 1 to 1.6 from the perspective of improving the effect of the Group I element and Nb2O5 and / or Ta2O5 functioning as a whole, being able to impart better machinability, being able to suppress the consumption of processing tools, and being able to further increase the number of dental prostheses obtained by continuous processing using one processing tool.

[0098] In the zirconium oxide composite sintered body of the present invention, the content of TiO2 is preferably greater than 0 mass% and less than 5.0 mass%, more preferably greater than 0.01 mass% and less than 4.5 mass%, relative to the total of 100 mass% of ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconium oxide, and Nb2O5 and Ta2O5, and from the perspective of functioning as a whole when combined with Group I elements and having better strength, it is further preferably greater than 0.6 mass% and less than 4.3 mass%, particularly preferably greater than 0.7 mass% and less than 3.7 mass%, and most preferably greater than 2.5 mass% and less than 3.5 mass%.

[0099] As some suitable embodiments, there can be mentioned a zirconia composite sintered body, which includes ZrO2, HfO2, a stabilizer capable of suppressing the phase transformation of zirconia, and Nb2O5 and / or Ta2O5,

[0100] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,

[0101] The total content of ZrO2 and HfO2 is 78-97.5 mol%.

[0102] The content of the stabilizer is 1 to 12 mol%.

[0103] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.

[0104] The zirconia composite sintered body further comprises Group I elements and TiO2,

[0105] The stabilizer comprises Y2O3 and / or CeO2,

[0106] The content of TiO2 is 0.6 mass % or more and 4.3 mass % or less,

[0107] The content of the Group I element is greater than 0 mol % and less than 3 mol % relative to 100 mol % of the total of ZrO 2 , HfO 2 , the stabilizer, Nb 2 O 5 and Ta 2 O 5 ,

[0108] When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.

[0109] In the aforementioned suitable embodiment, as described above, the total content of ZrO2 and HfO2, the type and content of the stabilizer, the total content of Nb2O5 and Ta2O5, the type and content of the Group I element, the content of TiO2, and the ratio of A / B can be appropriately changed.

[0110] The average grain size of the zirconia composite sintered body of the present invention is preferably 0.5 to 5.0 μm, more preferably 0.5 to 4.5 μm, and even more preferably 1.0 to 4.0 μm from the viewpoint of better machinability. The method for measuring the average grain size is described in the examples described below.

[0111] The average grain size can be measured by adjusting the number of particles so that the number of particles included in the SEM photograph image of one field of view is about 50 or 100 in the method described in the Examples.

[0112] The density of the zirconia composite sintered body is preferably 5.5 g / cm2 because the higher the density, the fewer the internal voids, the less likely it is to scatter light, the better the light transmittance, and the better the strength. 3 More preferably, 5.7 g / cm 3 More preferably, 5.9 g / cm 3 above.

[0113] It is particularly preferred that the zirconia composite sintered body contains substantially no voids.

[0114] The density of the composite sintered body can be calculated by (mass of the composite sintered body) / (volume of the composite sintered body).

[0115] As another embodiment of the present invention, there is mentioned a method for producing a zirconia composite sintered body, which comprises:

[0116] A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5,

[0117] In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5,

[0118] The total content of ZrO2 and HfO2 is 78-97.5 mol%.

[0119] The content of the stabilizer is 1 to 12 mol%.

[0120] The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%.

[0121] Also comprising a raw material compound of a Group I element and TiO2; and

[0122] A step of sintering the molded body.

[0123] The raw material composition of the zirconia composite sintered body includes ZrO2, HfO2, a stabilizer capable of inhibiting the phase transformation of zirconia, Nb2O5 and / or Ta2O5, a raw material compound of a Group I element, and TiO2. The raw material composition of the zirconia composite sintered body may be in a dry state, or in a state containing a liquid or in a state contained in a liquid. The raw material composition may be in the form of, for example, powder, granules or granules, paste, slurry, etc.

[0124] The raw material composition contains a raw material compound of a Group I element so that the obtained zirconium oxide composite sintered body contains the Group I element. Examples of the raw material compound of a Group I element include hydroxides and / or salts of Group I elements.

[0125] Examples of the hydroxide of the Group I element include lithium hydroxide, sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, and francium hydroxide.

[0126] Examples of salts of Group I elements include carbonates and hydrogen carbonates.

[0127] Examples of the carbonate of the Group I element include lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, francium carbonate, and cesium carbonate.

[0128] Examples of the hydrogen carbonate salt of the Group I element include lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, rubidium hydrogen carbonate, francium hydrogen carbonate, and cesium hydrogen carbonate.

[0129] The hydroxide and salt of the Group I element may be used alone or in combination of two or more.

[0130] For ZrO2 and HfO2, commercially available zirconium oxide powder can be used. Examples of commercially available products include zirconium oxide powder (trade name "Zpex (registered trademark)" (content of Y2O3: 3 mol%), "Zpex (registered trademark) 4" (content of Y2O3: 4 mol%), "Zpex (registered trademark) 4Smile (registered trademark)" (content of Y2O3: 5.5 mol%), "TZ-3Y" (content of Y2O3: 3 mol%), "TZ-3YS" (content of Y2O3: 3 mol%), "TZ-4YS" (content of Y2O3: 4 mol%), "TZ-6Y" (content of Y2O3: 6 mol%), "TZ-6YS" (content of Y2O3: 6 mol%), "TZ-8YS" (content of Y2O3: 8 ... Z-10YS" (content of Y2O3: 10 mol%), "TZ-3Y-E" (content of Y2O3: 3 mol%), "TZ-3YS-E" (content of Y2O3: 3 mol%), "TZ-3YB-E" (content of Y2O3: 3 mol%), "TZ-3YSB-E" (content of Y2O3: 3 mol%), "TZ-3YB" (content of Y2O3: 3 mol%), "TZ-3YSB" (content of Y2O3: 3 mol%), "TZ-3Y20AB" (content of Y2O3: 3 mol%), "TZ-8YSB" (content of Y2O3: 8 mol%), "TZ-0" (content of Y2O3: 0 mol%); all of the above are manufactured by Tosoh Corporation), etc. The aforementioned commercially available zirconia powder also contains HfO2. As a commercial product, a product containing Y2O3 may also be used. As the zirconium oxide powder, in the raw material composition of the present invention, a zirconium oxide powder in which Y2O3 is uniformly dispersed and solid-dissolved, such as the aforementioned commercial product TZ series (part of the product name contains "TZ"), may also be used.

[0131] The method for producing the zirconium oxide powder is not particularly limited, and for example, a known method such as a fracturing process in which coarse particles are crushed into fine powder, or a deposition process in which atoms or ions form nuclei and synthesize the particles through a growth process can be used.

[0132] The type of zirconium oxide powder in the raw material composition is not particularly limited. The zirconium oxide powder contains ZrO2 and HfO2. When no stabilizer is contained or when the content of the stabilizer is increased as required, stabilizer particles can be added separately. The stabilizer particles are not particularly limited as long as the content of the stabilizer contained in the zirconium oxide composite sintered body can be adjusted to the above-specified range.

[0133] As the particles of the stabilizer, for example, a commercially available product may be used, or a powder of a commercially available product may be pulverized using a known pulverizing and mixing device (such as a ball mill) and then used.

[0134] The aforementioned stabilizer may be either a stabilizer that is insoluble in ZrO 2 and HfO 2 or a stabilizer that is soluble in ZrO 2 and HfO 2 .

[0135] In some suitable embodiments, a method for producing a zirconia composite sintered body can be cited, wherein, in the raw material composition, from the aspect of being a reason for easily obtaining the target zirconia composite sintered body, the stabilizer (suitably Y2O3) contains a stabilizer that is not soluble in ZrO2 and HfO2. For example, it can be confirmed by an X-ray diffraction (XRD; X-Ray Diffraction) pattern that the stabilizer contains a stabilizer that is not soluble in zirconia.

[0136] When a peak derived from a stabilizer is confirmed in the XRD pattern of the raw material composition or the molded body, a stabilizer that is not solid-soluble in ZrO 2 and HfO 2 exists in the raw material composition or the molded body.

[0137] When the entire amount of stabilizer is solid-dissolved in ZrO2 and HfO2, the peak derived from the stabilizer cannot be confirmed in the XRD pattern. However, depending on conditions such as the crystal state of the stabilizer, the stabilizer may not be solid-dissolved in ZrO2 and HfO2 even if the peak of the stabilizer is not present in the XRD pattern.

[0138] The case where the stabilizer contains a stabilizer that is not soluble in ZrO 2 and HfO 2 is described below using yttrium oxide as an example.

[0139] In the raw material composition or the molded body of the present invention, the existence ratio of yttrium oxide that is not dissolved in ZrO2 and HfO2 (hereinafter sometimes referred to as "undissolved yttrium oxide") is y It can be calculated based on the following mathematical formula (1).

[0140] f y =I 29 / (I 28 +I 29 +I 30 )×100

[0141] (where f y Indicates the proportion of undissolved yttrium oxide (%). In XRD measurement, I 28 The area intensity of the peak near 2θ = 28° where the main peak of the monoclinic system appears, I 29 The area intensity of the peak near 2θ = 29° where the main peak of yttrium oxide appears, I 30 Indicates the area intensity of the peak near 2θ=30° where the main peak of the tetragonal or cubic system appears.

[0142] In addition, when a stabilizer other than yttrium oxide is used simultaneously, by replacing I 29 Substituting the peaks of other stabilizers can also be used to calculate the undissolved existence rate of stabilizers other than yttrium oxide.

[0143] From the viewpoint of easily obtaining the target zirconia composite sintered body, etc., the existence ratio of undissolved yttrium oxide f y It is preferably greater than 0%, more preferably 1% or more, further preferably 2% or more, and particularly preferably 3% or more. y The upper limit of γ may be, for example, 25% or less, but it preferably depends on the content of yttrium oxide in the raw material composition or the molded body.

[0144] For example, when the content of yttrium oxide in the raw material composition or the molded body of the present invention is 3 mol% or more and 8 mol% or less, it is as follows.

[0145] When the content of yttrium oxide is 3 mol% or more and less than 4.5 mol%, f y When the content of yttrium oxide is 4.5 mol% or more and less than 5.8 mol%, f y When the content of yttrium oxide is 5.8 mol% or more and 8 mol% or less, f y It can be set to 25% or less.

[0146] For example, when the content of yttrium oxide is 3 mol% or more and less than 4.5 mol%, f y It is preferably 2% or more, more preferably 3% or more, further preferably 4% or more, and particularly preferably 5% or more.

[0147] When the content of yttrium oxide is 4.5 mol% or more and less than 5.8 mol%, f y It is preferably 3% or more, more preferably 4% or more, further preferably 5% or more, further preferably 6% or more, and particularly preferably 7% or more.

[0148] When the content of yttrium oxide is 5.8 mol% or more and 8 mol% or less, f y It is preferably 4% or more, more preferably 5% or more, further preferably 6% or more, further preferably 7% or more, and particularly preferably 8% or more.

[0149] In the raw material composition or the molded body of the present invention, the stabilizer may not be solid-dissolved in ZrO2 and HfO2 at all. It should be noted that in the present invention, the so-called solid-dissolved stabilizer means, for example, that the elements (atoms) contained in the stabilizer are solid-dissolved in ZrO2 and HfO2.

[0150] The Nb2O5 and / or Ta2O5 added to the raw material composition of the present invention is not particularly limited as long as it can adjust the content of Nb2O5 and / or Ta2O5 contained in the zirconia composite sintered body to the above-mentioned specified range. Nb2O5 and / or Ta2O5 are not particularly limited, for example, commercial products can be used, and powders of commercial products can also be crushed using a known crushing and mixing device (ball mill, etc.) and then used.

[0151] As a process for preparing the raw material composition, for example, there can be cited a method of wet mixing the raw materials of the aforementioned raw material composition (ZrO2, HfO2, stabilizer, Nb2O5 and / or Ta2O5, raw material compounds of Group I elements (for example, hydroxides and / or salts of Group I elements), and TiO2) in a solvent containing water to obtain the raw material composition.

[0152] The shape of TiO2 added to the raw material composition is not particularly limited, and may be granular, needle-shaped, or the like, but granular is preferred from the viewpoint of better machinability and greater number of pieces obtained through continuous processing of the sintered body.

[0153] In the case where the TiO2 added to the raw material composition is granular TiO2, the average particle size of TiO2 is not particularly limited as long as the effect of the present invention is achieved because it is crushed after the raw materials are mixed, and can be 7 nm or more, or 100 μm or less. The reason for not limiting the average particle size of granular TiO2 is that when mixed with powders of other raw material components, the powders are crushed until the desired average particle size is reached, so there is no reason to limit the granular TiO2 added as a raw material.

[0154] The average particle size of TiO2 is preferably 10 nm or more, more preferably 20 nm or more, and further preferably 30 nm or more, from the viewpoint of being easy to obtain excellent machinability and being easy to increase the number obtained by continuous processing of sintered bodies. In addition, the average particle size of TiO2 is preferably 50 μm or less, more preferably 20 μm or less, and further preferably 10 μm or less, from the viewpoint of being easy to obtain excellent machinability and being easy to increase the number obtained by continuous processing of sintered bodies.

[0155] The average particle size of TiO2 can be obtained by laser diffraction scattering method or electron microscope observation of particles. Specifically, for the particle size measurement above 0.1 μm, laser diffraction scattering method is simple, and for the particle size measurement of ultrafine particles less than 0.1 μm, electron microscope observation is simple. 0.1 μm is a measured value based on laser diffraction scattering method. It should be noted that in the case of particles formed by the aggregation of primary particles such as agglomerated particles, there is an average particle size of primary particles and an average particle size of secondary particles, but as the average particle size of filler, it is set to the average particle size of secondary particles whose particle size becomes large.

[0156] Specifically, the laser diffraction scattering method can be measured on a volume basis using, for example, a laser diffraction particle size distribution measuring apparatus (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium.

[0157] Specifically, electron microscope observation can be obtained by, for example, taking electron microscope (Hitachi, Ltd., S-4000 type) photos of particles, using image analysis type particle size distribution measurement software (Mac-View (Mac-View, Ltd., Mac-Tech)) to measure the particle diameter of particles (more than 200) observed in the unit visual field of the photo. At this time, particle diameter is obtained as the arithmetic mean of the longest length and the shortest length of the particle, and the average particle diameter is calculated by the number of particles and its particle diameter.

[0158] The method for wet mixing the aforementioned raw materials in a solvent containing water is not particularly limited. For example, the raw materials can be wet-mixed by a known pulverizing and mixing device (ball mill, etc.) to form a slurry, and then the slurry is dried and granulated to prepare a granular raw material composition.

[0159] In the wet mixing step, additives such as a binder, a plasticizer, a dispersant, an emulsifier, a defoamer, a pH adjuster, and a lubricant may be further contained. The additives may be used alone or in combination of two or more.

[0160] For the aforementioned binder, a primary powder formed by a mixture of ZrO2, HfO2, Y2O3, Nb2O5 and / or Ta2O5, hydroxides and / or salts of Group I elements, and TiO2 can be added to water to prepare a slurry, which can then be added to the crushed slurry.

[0161] The aforementioned adhesive is not particularly limited, and known adhesives can be used. As the adhesive, for example, polyvinyl alcohol-based adhesives, acrylic adhesives, wax-based adhesives (paraffin, etc.), methylcellulose, carboxymethylcellulose, polyvinyl butyral, polymethyl methacrylate, ethylcellulose, polyethylene, polypropylene, ethylene-vinyl acetate copolymer, polystyrene, atactic polypropylene, methacrylic resins, etc. can be cited.

[0162] Examples of the plasticizer include polyethylene glycol, glycerin, propylene glycol, and dibutyl phthalate.

[0163] Examples of the dispersant include ammonium polycarboxylates (triammonium citrate, etc.), ammonium polyacrylates, acrylic copolymer resins, acrylate copolymers, polyacrylic acid, bentonite, carboxymethyl cellulose, anionic surfactants (e.g., polyoxyethylene alkyl ether phosphates such as polyoxyethylene lauryl ether phosphate, etc.), nonionic surfactants, olein, amine salt-type surfactants, oligosaccharide alcohols, and stearic acid.

[0164] Examples of the emulsifier include alkyl ethers, phenyl ethers, and sorbitan derivatives.

[0165] Examples of the defoaming agent include alcohol, polyether, silicone, wax, and the like.

[0166] Examples of the pH adjuster include ammonia, ammonium salts (including ammonium hydroxide such as tetramethylammonium hydroxide), and the like.

[0167] Examples of the lubricant include polyoxyethylene alkyl ether and wax.

[0168] The solvent used in wet mixing is not particularly limited as long as it contains water, and an organic solvent, a mixed solvent of water and an organic solvent, or water alone can be used. Examples of the organic solvent include ketone solvents such as acetone and ethyl methyl ketone; alcohol solvents such as ethanol, 1-propanol, 2-propanol, 2-methyl-2-propanol, glycerol, diglycerol, polyglycerol, propylene glycol, dipropylene glycol, polypropylene glycol, ethylene glycol, diethylene glycol, polyethylene glycol, polyethylene glycol monomethyl ether, 1,2-pentanediol, 1,2-hexanediol, and 1,2-octanediol.

[0169] The raw material composition of the zirconia composite sintered body used in the present invention may contain other components besides ZrO2, Y2O3, Nb2O5, Ta2O5, hydroxides and / or salts of Group I elements, and TiO2 as long as it achieves the effect of the present invention. Examples of such other components include colorants (pigments and composite pigments), fluorescent agents, and SiO2. Other components may be used alone or in combination of two or more.

[0170] Examples of the pigment include oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.), preferably oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, and Tb, and more preferably oxides of at least one element selected from V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Tb. However, Y2O3 and CeO2 may be removed from the pigment.

[0171] Examples of the composite pigment include (Zr, V)O2, Fe(Fe, Cr)2O4, (Ni, Co, Fe)(Fe, Cr)2O4·ZrSiO4, and (Co, Zn)Al2O4.

[0172] Examples of the fluorescent agent include Y2SiO5:Ce, Y2SiO5:Tb, (Y, Gd, Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, BaMgAl 10 O 17 :Eu et al.

[0173] Next, the obtained raw material composition is molded to produce a molded body. The molding method is not particularly limited, and a known method (such as press molding) can be used.

[0174] When the zirconia molded body is produced by a method including the step of press-molding the raw material composition, the specific method of press-molding is not particularly limited, and a known press-molding machine can be used for the press-molding. Specific methods of press-molding include, for example, uniaxial pressing.

[0175] The pressurization pressure is appropriately set to an optimal value according to the size of the target molded body, the porosity, the biaxial bending strength, and the particle size of the raw material powder, and is usually 5 MPa or more and 1000 MPa or less. By increasing the pressurization pressure during molding in the aforementioned manufacturing method, the pores of the obtained molded body are further filled, the porosity can be set lower, and the density of the molded body can be increased. In addition, in order to increase the density of the obtained zirconia molded body, cold isostatic pressing (CIP) treatment can be further performed after uniaxial pressing.

[0176] Next, the obtained compact is sintered.

[0177] The term "molded body" refers to a molded body that has not reached any of the semi-sintered state (pre-fired state) and the sintered state. That is, the molded body is formed into a molded body but is not fired, and is distinguished from a pre-fired body and a sintered body in this respect.

[0178] The sintering temperature (maximum sintering temperature) for obtaining the zirconia composite sintered body is, for example, preferably 1300°C or higher, more preferably 1350°C or higher, further preferably 1400°C or higher, further preferably 1450°C or higher, and particularly preferably 1500°C or higher. In addition, the sintering temperature is, for example, preferably 1680°C or lower, more preferably 1650°C or lower, and further preferably 1600°C or lower. As the method for producing the zirconia composite sintered body of the present invention, it is preferred that the formed body be sintered at a maximum sintering temperature of 1300 to 1680°C. The aforementioned maximum sintering temperature is preferably a temperature in the atmosphere.

[0179] The holding time (retention time) at the maximum sintering temperature also depends on the temperature, but is preferably less than 30 hours, more preferably less than 20 hours, further preferably less than 10 hours, further preferably less than 5 hours, particularly preferably less than 3 hours, and most preferably less than 2 hours. Furthermore, the holding time may also be set to less than 25 minutes, less than 20 minutes or less than 15 minutes. In addition, the holding time is preferably more than 1 minute, more preferably more than 5 minutes, and more preferably more than 10 minutes. According to the manufacturing method of the present invention, according to the content of the stabilizer, a zirconia composite sintered body with excellent bending strength, light transmittance and machinability can be produced. In addition, as long as the effect of the present invention can be obtained, the sintering time can also be shortened. By shortening the sintering time, production efficiency can be improved while reducing energy costs.

[0180] In the method for producing a zirconia composite sintered body of the present invention, when the molded body is sintered, the heating rate is not particularly limited, but is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and further preferably 0.5°C / min or more. In addition, the heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and further preferably 20°C / min or less. By making the heating rate above the lower limit, productivity is improved.

[0181] In the process of sintering the molded body, a general dental zirconia sintering furnace can be used. As a dental zirconia sintering furnace, a commercial product can also be used. As commercial products, Noritake KATANA (registered trademark) F-1, F-1N, F-2 (the above are SK Medical Electronics Co., Ltd.) and the like can be cited.

[0182] Furthermore, the step of sintering the formed body preferably includes a step of performing a hot isostatic pressing (HIP) treatment in addition to the sintering at the highest sintering temperature. The HIP treatment can further improve the light transmittance and strength of the zirconia composite sintered body.

[0183] Hereinafter, the sintered body obtained by sintering at the above-mentioned maximum sintering temperature is referred to as a "primary sintered body", and the sintered body after HIP treatment is referred to as a "HIP treatment sintered body".

[0184] The HIP treatment can be performed using a known hot isostatic pressing (HIP) apparatus.

[0185] The temperature of the HIP treatment is not particularly limited, but from the perspective of obtaining a high-strength, dense zirconia composite sintered body, the HIP temperature is preferably 1200° C. or higher, more preferably 1300° C. or higher, and further preferably 1400° C. or higher. In addition, the HIP temperature is preferably 1700° C. or lower, more preferably 1650° C. or lower, and further preferably 1600° C. or lower.

[0186] In the method for producing a zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP pressure is not particularly limited. From the perspective of obtaining a dense sintered body with high strength, the HIP pressure is preferably 100 MPa or more, more preferably 125 MPa or more, and further preferably 130 MPa or more. In addition, the upper limit of the HIP pressure is not particularly limited, and can be, for example, 400 MPa or less, 300 MPa or less, and further 200 MPa or less.

[0187] In the method for producing a zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the heating rate is not particularly limited, but is preferably 0.1°C / min or more, more preferably 0.2°C / min or more, and further preferably 0.5°C / min or more. In addition, the heating rate is preferably 50°C / min or less, more preferably 30°C / min or less, and further preferably 20°C / min or less. By making the heating rate above the lower limit, productivity is improved.

[0188] In the method for producing a zirconia composite sintered body of the present invention, when the primary sintered body is subjected to HIP treatment, the HIP time is not particularly limited. From the perspective of obtaining a high-strength and dense zirconia composite sintered body, the HIP treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. In addition, the HIP treatment time is preferably 10 hours or less, more preferably 6 hours or less, and even more preferably 3 hours or less.

[0189] In the method for manufacturing a zirconium oxide composite sintered body of the present invention, when the aforementioned primary sintered body is subjected to HIP treatment, the pressure medium is not particularly limited. From the viewpoint of having a low impact on zirconium oxide, the pressure medium can be selected from at least one of oxygen, oxygen containing 3% hydrogen, air and an inert gas (such as nitrogen, argon, etc.).

[0190] When the primary sintered body is subjected to the HIP treatment in an oxygen mixed gas atmosphere, the oxygen concentration is not particularly limited, and may be, for example, greater than 0% and not more than 20%.

[0191] When the oxygen mixed gas is used, as a gas other than oxygen, at least one inert gas (for example, nitrogen, argon, etc.) can be selected.

[0192] In the method for manufacturing a zirconia composite sintered body of the present invention, if the aforementioned HIP treatment is performed in a reducing atmosphere using an inert gas or the like, blackening may sometimes occur due to oxygen defects. In this case, in order to remove the blackening, it is preferably included in a step of heat treatment in the air or in an oxygen-excess atmosphere at a temperature below 1650°C after the aforementioned HIP treatment step (hereinafter also referred to as "tempering treatment"), and from the viewpoint of effectively performing the heat treatment, it is more preferably performed in an oxygen-excess atmosphere. An oxygen-excess atmosphere refers to an oxygen concentration greater than that in the air. As an oxygen-excess atmosphere, there is no particular limitation as long as the oxygen concentration is greater than 21% and less than 100%, and it can be appropriately selected from this range. For example, the oxygen concentration may also be set to 100%.

[0193] The zirconia composite sintered body of the present invention is not particularly limited as long as it can achieve the effects of the present invention, and may be a primary sintered body, a HIP-treated sintered body, or a tempered sintered body.

[0194] As some suitable embodiments, there can be mentioned a zirconia composite sintered body which is a sintered body after tempering treatment.

[0195] The temperature of the heat treatment in the air or in an oxygen-excess atmosphere may be appropriately changed depending on the aesthetic properties of the zirconia composite sintered body (for example, the color of a dental prosthesis).

[0196] In certain suitable embodiments, from the viewpoint of the aesthetics of the zirconia composite sintered body, the temperature of the heat treatment in air or in an oxygen-excess atmosphere is preferably 1650° C. or lower, more preferably 1600° C. or lower, and further preferably 1550° C. or lower.

[0197] In other suitable embodiments, from the viewpoint of the aesthetics of the zirconia composite sintered body, the temperature of the heat treatment in air or in an oxygen-excess atmosphere is preferably 1400° C. or lower, more preferably 1300° C. or lower, and further preferably 1200° C. or lower.

[0198] Furthermore, in any embodiment, the temperature of the heat treatment is preferably 500° C. or higher, more preferably 600° C. or higher, and even more preferably 700° C. or higher.

[0199] In the above-mentioned tempering treatment, a general dental zirconia firing furnace can be used. As a dental zirconia firing furnace, a commercial product can also be used. As commercial products, Noritake KATANA (registered trademark) F-1, F-1N, F-2 (the above are SK Medical Electronics Co., Ltd.) and the like can be cited.

[0200] The zirconia composite sintered body of the present invention is a sintered body, but has excellent machinability, and therefore does not need to be sintered after machining a semi-sintered pre-calcined body in a ground state to obtain a sintered body.

[0201] On the other hand, as a method for producing a zirconia composite sintered body, a method may be adopted in which a molded body obtained using the raw material composition is pre-sintered to produce a semi-sintered pre-sintered body, and the unprocessed pre-sintered body is machined to produce a sintered body.

[0202] As some other embodiments, there is provided a method for producing a zirconia composite sintered body, which includes: a step of preparing a formed body using the raw material composition, a step of pre-firing the obtained formed body to obtain a zirconia calcined body (pre-firing step), and a step of sintering the zirconia calcined body.

[0203] In order to reliably perform agglomeration, the firing temperature (pre-firing temperature) in the pre-firing step is, for example, preferably 800° C. or higher, more preferably 900° C. or higher, and further preferably 950° C. or higher.

[0204] The calcining temperature is preferably, for example, 1200° C. or less, more preferably 1150° C. or less, and further preferably 1100° C. or less. The calcining temperature is preferably, for example, 800° C. to 1200° C. It is believed that at such a calcining temperature, the stabilizer will not be dissolved to a large extent during the calcining step.

[0205] The calcined zirconium oxide of the present invention refers to a state in which ZrO2 particles are necked (fixed) to each other and the ZrO2 particles (powder) are not completely sintered (semi-sintered state).

[0206] The density of the calcined zirconium oxide is preferably 2.7 g / cm 3 In addition, the density of the zirconia calcined body is preferably 4.0 g / cm 3 Below, more preferably 3.8 g / cm 3 Below, more preferably 3.6 g / cm 3When the density is within this range, processing can be easily performed. The density of the calcined body can be calculated, for example, in the form of (mass of the calcined body) / (volume of the calcined body).

[0207] The three-point bending strength of the calcined zirconium oxide body is preferably 15 to 70 MPa, more preferably 18 to 60 MPa, and even more preferably 20 to 50 MPa.

[0208] The bending strength can be measured as follows: using a test piece of thickness 5mm×width 10mm×length 50mm, except for the size of the test piece, the test is performed in accordance with ISO 6872:2015. The surface of the test piece and the C surface (the surface obtained by chamfering the corner of the test piece at an angle of 45°) are surface-finished along the length direction using 600 sandpaper. The test piece is configured in a manner that the widest surface faces the vertical direction (load direction). In the bending test measurement, the span is set to 30mm and the crosshead speed is set to 1.0mm / minute.

[0209] The step of sintering the zirconia calcined body can be performed by the same method and conditions (temperature, pressure, etc.) as the step of sintering the molded body. Therefore, in the embodiment of the manufacturing method using the zirconia calcined body, the "molded body" may be replaced with the "calcined body".

[0210] The zirconia composite sintered body of the present invention has excellent strength. The biaxial bending strength of the zirconia composite sintered body of the present invention is preferably 350 MPa or more, more preferably 400 MPa or more, further preferably 450 MPa or more, further preferably 450 MPa or more, and particularly preferably 500 MPa or more. By making the zirconia composite sintered body of the present invention have such biaxial bending strength, for example, when used as a dental prosthesis, it can suppress breakage in the oral cavity. There is no particular restriction on the upper limit of the biaxial bending strength, but the biaxial bending strength can be set to, for example, 1200 MPa or less, and further 1000 MPa or less. It should be noted that the biaxial bending strength of the zirconia composite sintered body can be measured according to ISO 6872:2015.

[0211] The zirconia composite sintered body of the present invention preferably has high light transmittance. Light transmittance can be evaluated by ΔL*. Regarding light transmittance, specifically, the zirconia composite sintered body of the present invention preferably has a ΔL* of 10 or more when the diameter is 15 mm and the thickness is 1.2 mm, more preferably 12 or more, further preferably 13 or more, and particularly preferably 14 or more. By making the ΔL* within the above range, a zirconia composite sintered body with high light transmittance can be obtained.

[0212] ΔL* refers to the difference between the brightness of the same sample under a white background (first L* value) and the brightness under a black background (second L* value). Specifically, it refers to the difference between the L* value under a white background (JIS Z 8781-4:2013 Color Measurement-Part 4: CIE1976 L*a*b* Color Space) and the L* value under a black background. The white background refers to the white part of the obscuration test paper described in JIS K 5600-4-1:1999 Part 4 Section 1, and the black background refers to the black part of the aforementioned obscuration test paper.

[0213] The upper limit of ΔL* is not particularly limited, and may be, for example, 25 or less, and may further be 20 or less from the viewpoint of aesthetics.

[0214] It should be noted that ΔL* when the zirconia composite sintered body has a diameter of 15 mm and a thickness of 1.2 mm can be measured using a spectrophotometer, for example, a dental colorimetric device ("Crystaleye CE100-CE / JP", 7-band LED light source, and analysis software "Crystaleye" (manufactured by Olympus Corporation)).

[0215] As dental prostheses manufactured using the zirconia composite sintered body of the present invention, for example, in addition to crown restorations such as inlays, onlays, veneers, crowns, core crowns, bridges, etc., abutments, dental posts, dentures, denture bases, implant components (fixtures, bases), etc. can also be cited. In addition, machining is preferably performed using, for example, a commercially available dental CAD / CAM system. As examples of the CAD / CAM system, the CEREC system manufactured by Dentsply Sirona Dental Systems Co., Ltd. and the "KATANA (registered trademark) system" manufactured by Kuraray Noritake Dental Co., Ltd. can be cited.

[0216] Furthermore, the zirconia composite sintered body of the present invention can be used for applications other than dental applications, and is particularly suitable for zirconia components that require a different or complex shape and strength.

[0217] Compared with sintered bodies manufactured only by existing manufacturing methods (injection molding, CIP, casting molding or 3D printing, etc.), the zirconia composite sintered body of the present invention can directly process the sintered body. Therefore, it is economical to obtain the desired zirconia component in a short time, for example. In the case of complex-shaped parts that are difficult to manufacture by previous manufacturing methods, it is not necessary to obtain multiple components by mechanical interlocking, so that a zirconia component with high strength can be obtained. Furthermore, since the sintered body can be directly processed, when dimensional accuracy is required, there is no need for a sintering process, and there is no uneven firing shrinkage, so that the zirconia component can be obtained with high precision. Specifically, it can also be used as a method for manufacturing jewelry decoration purposes, engine components and internal components for aircraft, automobiles, etc., frame materials for display panels, building components, electrical product components, household goods components, and toy components.

[0218] Furthermore, the present zirconia component may be used as a composite component by fitting it with a different type of material.

[0219] The present invention includes various embodiments in which all or part of the above-described configurations are combined within the scope of the technical concept of the present invention as long as the effects of the present invention are achieved.

[0220] Example

[0221] Hereinafter, the present invention will be further specifically described by giving examples, but the present invention is not limited to these examples, and a person with common knowledge in the art can make various modifications within the scope of the technical concept of the present invention. It should be noted that in the following examples and comparative examples, the average particle size is the average primary particle size, which can be obtained by a laser diffraction scattering method. Specifically, a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) can be used to measure a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium on a volume basis.

[0222] [Examples 1 to 34 and Comparative Examples 1 to 8]

[0223] The measurement samples of the examples and comparative examples were produced through the steps of producing a granular raw material composition, producing a compact, and producing a sintered body (producing a primary sintered body, HIP treatment, and tempering treatment).

[0224] [Preparation of Granular Raw Material Composition]

[0225] In order to prepare the granular raw material composition of each embodiment and comparative example, commercially available ZrO2 powder, Y2O3 powder, Nb2O5 powder, Ta2O5 powder, TiO2 powder, and raw material compounds of the first group element are mixed to form the composition described in Tables 1 to 3, water is added to prepare a slurry, and wet pulverization and mixing are carried out with a ball mill until the average particle size becomes less than 0.13 μm. After adding a binder to the pulverized slurry, it is dried with a spray dryer to prepare a granular raw material composition (hereinafter also referred to as "raw material composition") for the manufacture of the molded body described later. The above average particle size is a value measured by a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium and measured on a volume basis.

[0226] It should be noted that in Example 5, TZ-3Y (Y2O3 content: 3 mol%):TZ-6Y (Y2O3 content: 6 mol%) = 18.7:81.3 were mixed, and the ratio of each component was adjusted to become the blending ratio described in Table 1.

[0227] [Production of Molded Body]

[0228] For each of the Examples and Comparative Examples, a pellet-shaped molded body and a block-shaped molded body were produced as follows to obtain sintered body samples for evaluation of light transmittance and strength and for evaluation of processability.

[0229] For the pellet-shaped compact, a cylindrical mold having a diameter of 19 mm was used, and the raw material composition was placed in the mold so that the thickness of the zirconium oxide composite sintered body after sintering was 1.2 mm.

[0230] Next, the raw material composition was press-formed at a surface pressure of 200 MPa using a uniaxial press-forming machine to produce a pellet-shaped compact.

[0231] In addition, for the block-shaped compact, the raw material composition was placed in a mold having an inner dimension of 19 mm×18 mm so that the height of the zirconia composite sintered body after sintering was 14.5 mm.

[0232] Next, the raw material composition was press-formed at a surface pressure of 200 MPa using a uniaxial press-forming machine to produce a block-shaped compact.

[0233] [Production of primary sintered body]

[0234] The obtained particle-shaped and block-shaped formed bodies were kept in the atmosphere at the highest sintering temperature listed in Tables 1 to 3 for 2 hours using the sintering furnace "Noritake KATANA (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., to obtain particle-shaped and block-shaped zirconium oxide composite sintered body (primary sintered body) samples.

[0235] [Production of HIP-treated sintered body]

[0236] For the obtained particle-shaped and block-shaped zirconium oxide composite sintered bodies (primary sintered bodies), the HIP device "O2-Dr.HIP" manufactured by Kobe Steel, Ltd. was used to retain the bodies at the HIP temperature listed in Tables 1 to 3 at 150 MPa for 2 hours, thereby obtaining samples of particle-shaped and block-shaped zirconium oxide composite sintered bodies (HIP treated sintered bodies).

[0237] [Production of zirconia composite sintered body (sintered body after tempering)]

[0238] The obtained zirconia composite sintered bodies in particle shape and block shape (HIP treated sintered bodies) were retained at 700°C for 60 hours using a sintering furnace "Noritake KATANA (registered trademark) F-1" manufactured by SK Medical Electronics Co., Ltd., thereby obtaining samples of zirconia composite sintered bodies in particle shape and block shape (sintered bodies after tempering treatment). The size of the obtained samples was 15 mm in diameter × 1.2 mm in thickness for the particle shape and 15.7 mm in width × 16.5 mm in length × 14.5 mm in height for the block shape.

[0239] In addition, the content rate of each component of the sintered compact in Table 1 - Table 3 is the value calculated from the charge amount of a raw material.

[0240] The contents (mol %) of the Group I elements in Tables 1 to 3 are external addition rates relative to 100 mol % of the total of ZrO 2 , HfO 2 , the aforementioned stabilizers, Nb 2 O 5 , and Ta 2 O 5 .

[0241] The contents (mol%) of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5, and Ta2O5 in Tables 1 to 3 are the contents of each component in the total of 100 mol% of ZrO2, HfO2, the aforementioned stabilizer, Nb2O5, and Ta2O5. Only for ZrO2 and HfO2, it is expressed as the total content of ZrO2 and HfO2.

[0242] The content (mass %) of TiO2 in Tables 1 to 3 is the external addition rate relative to the total of 100 mass % of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5.

[0243] A / B in Tables 1 to 3 represents the ratio of A to B when the content of Y2O3 is A mol % and the total content of Nb2O5 and Ta2O5 is B mol %.

[0244] [Evaluation of light transmittance of zirconia composite sintered body]

[0245] The sample (diameter about 15 mm×thickness 1.2 mm) of the particle-shaped zirconia composite sintered body (sintered body after tempering treatment) of each example and comparative example was used as it is, and the light transmittance was evaluated by the following method (n=3). As a measuring device, a dental colorimetric device "Crystaleye" (7-band LED light source) manufactured by Olympus Corporation was used. First, the background (underlay) of the sample was set to white (the side opposite to the measuring device with respect to the sample was set to white), and the L* value of the L*a*b* colorimetric system (JIS Z 8781-4:2013 Colorimetry-Part 4: CIE 1976 L*a*b* color space) was measured as the first L* value. Next, for the same sample for which the first L* value was measured, the background (underlay) of the sample was set to black (the side opposite to the measuring device with respect to the sample was set to black), and the L* value of the L*a*b* colorimetric system was measured as the second L* value.

[0246] In the present invention, the difference between the first L* value and the second L* value (the value after deducting the second L* value from the first L* value) is set as the light transmittance, expressed as ΔL*. If ΔL* is high, it means that the light transmittance is high, and if ΔL* is low, it means that the light transmittance is low. When measuring the color, the black and white used as the background (underlay) can use the obscuration test paper used for the measurement of coatings described in JIS K 5600-4-1:1999. The average value of ΔL* of each sample is shown as the result in Tables 1 to 3.

[0247] A value of 10 or more was considered acceptable as ΔL*.

[0248] [Strength Evaluation of Zirconia Composite Sintered Body]

[0249] The samples of the particle-shaped zirconia composite sintered bodies (tempered sintered bodies) of the examples and comparative examples were used as they are, and the biaxial bending strength (n=5) was measured in accordance with ISO6872:2015 using a universal testing machine "AGS-X" (manufactured by Shimadzu Corporation) with the crosshead speed set to 1.0 mm / min. The average values ​​are shown in Tables 1 to 3 as the measurement results. As for the strength, 350 MPa or more was considered acceptable.

[0250] [Strength Evaluation of Zirconia Composite Sintered Body]

[0251] The samples of the particle-shaped zirconia composite sintered bodies (tempered sintered bodies) of the examples and comparative examples were used as they are, and the biaxial bending strength (n=5) was measured in accordance with ISO6872:2015 using a universal testing machine "AGS-X" (manufactured by Shimadzu Corporation) with the crosshead speed set to 1.0 mm / min. The average values ​​are shown in Tables 1 to 3 as the measurement results. As for the strength, 350 MPa or more was considered acceptable.

[0252] [Method for measuring average grain size in sintered body]

[0253] In the particle-shaped zirconia composite sintered bodies (tempered sintered bodies) of each example and comparative example, a surface image was obtained using a scanning electron microscope (trade name "VE-9800", manufactured by KEYENCE Co., Ltd.). After recording the grain boundaries of each crystal particle on the obtained image, the average grain size was calculated by image analysis.

[0254] In the measurement of the average grain size, an image analysis software (trade name "Image-Pro Plus", manufactured by Bodong Co., Ltd.) is used to binarize the read SEM image, adjust the brightness range in a manner that the grain boundary becomes clear, and identify particles from the field of view (area). The grain size obtained using Image-Pro Plus refers to: for the length of the line segment obtained by connecting the contour lines passing through the center of gravity obtained by the contour lines of the crystal particles, the grain size obtained by measuring and averaging with the center of gravity as the center and with a scale of 2 degrees, in the SEM photo images (3 fields of view) of each embodiment and comparative example, the average value of the grain size of all particles not involving the end of the image is set as the average grain size (number basis) in the sintered body.

[0255] "Particles not involving the image ends" refers to particles within the SEM photo image except for particles whose outlines do not completely fall within the screen (particles whose outlines are disconnected at the upper, lower, left, and right boundaries). The grain size of all particles not involving the image ends is selected in Image-Pro Plus using the option to exclude particles on all boundaries.

[0256] The average grain size of the crystal particles in the zirconia composite sintered body of Example 1 was 2.7 μm, and the average grain size of the crystal particles in the zirconia composite sintered body of Example 14 was 2.2 μm.

[0257] [Evaluation of processability of zirconia composite sintered body]

[0258] For the samples of the block-shaped zirconia composite sintered body (sintered body after tempering treatment) of each embodiment and comparative example, 30 samples with a metal fixture bonded to the surface of about 15.7 mm in width × 14.5 mm in height were prepared and processed into the crown shape of a general front tooth using the CEREC system "MC-XL" (manufactured by Dentsply Sirona). The processing program used the software "inLab (registered trademark) CAM virsion 20.0.1.203841", selected Manufacturer: IVOCLARVIVADENT, Material name: IPS e.max CAD, Production Method: Grinding, Block size: C16, and the processing tools used were Step Bur 12 and Cylinder Pointed Bur 12S.

[0259] [Processing time]

[0260] The processing times shown in Tables 1 to 3 are the times required to complete processing of the first sample from the start of processing of the sample under the conditions described in the above [Evaluation of Processability of Zirconia Composite Sintered Body] using a new processing tool.

[0261] In addition, if an error occurs due to the load during processing and the CEREC system "MC-XL" stops processing, a new processing tool is replaced and processing is restarted. This operation is repeated until one sample is processed, and the required time is taken as the processing time.

[0262] [Number of pieces processed]

[0263] The number of samples processed shown in Tables 1 to 3 refers to the number of samples that can be processed into the crown shape of the front teeth without changing the processing tools once, using a new set of processing tools and starting the processing of the samples under the conditions described in the above [Evaluation of the processability of the zirconia composite sintered body]. The maximum number of samples used in the test was 30, and when 30 samples were processed with one processing tool, no additional processing test was performed, and it was always set as "30 or more".

[0264] In addition, before the processing of the first sample is completed, an error occurs due to the load during processing, etc., and the MC-XL stops processing in the middle, and then replaces it with a new processing tool and restarts the processing. Repeat this operation until one sample is processed, and the reciprocal of the number of processing tools used is taken as the number of processing. For example, "0.2" in Comparative Example 1 of Table 3 means that 5 processing tools are used to obtain a sample processed into the shape of a crown of a front tooth. The results are shown in the following Tables 1 to 3.

[0265]

[0266]

[0267]

[0268] From the above results, it was confirmed that the zirconia composite sintered body of the present invention has strength and light transmittance suitable for dental use and is excellent in machinability.

[0269] In Examples 1 to 34, the consumption of the processing tool can be suppressed, and the number of dental prostheses that can be continuously processed by one processing tool can be increased compared to the conventional art.

[0270] On the other hand, in Comparative Examples 1 and 2 which do not contain a Group I element, the reduction in processing time is insufficient.

[0271] In Comparative Examples 3 and 8 not containing TiO2, the strength was insufficient.

[0272] In Comparative Example 4 in which the content of Nb2O5 was too high and Comparative Example 7 in which the content of Y2O3 was too low, defects or peeling occurred in the samples, and physical properties could not be measured.

[0273] In Comparative Example 5, in which the content of Nb2O5 was too low, the processing time was not sufficiently shortened. In Comparative Example 6, in which the content of Y2O3 was too high, the processing time was not sufficiently shortened.

[0274] In addition, in Patent Document 1, if the addition amount of TiO2 is increased, the strength decreases in proportion to the addition amount (Figure 7). However, in the zirconia composite sintered body of the present invention, when containing Nb2O5 and / or Ta2O5 as components, by further containing Group I elements and TiO2, these components work as a whole to improve the transmittance and strength of the zirconia composite sintered body, and it can be confirmed that a zirconia composite sintered body with excellent machinability, transmittance and strength is obtained.

[0275] Industrial Applicability

[0276] The zirconia composite sintered body of the present invention has appropriate strength and light transmittance and is excellent in machinability, and is particularly useful as a dental material such as a dental prosthesis for dental treatment purposes.

Claims

1. A zirconia composite sintered body comprising ZrO2, HfO2, a stabilizer capable of inhibiting phase transformation of zirconia, and Nb2O5 and / or Ta2O5, In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5, The total content of ZrO2 and HfO2 is 78-97.5 mol%. The content of the stabilizer is 1 to 12 mol%. The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%. The zirconia composite sintered body further comprises a Group I element and TiO2.

2. The zirconia composite sintered body according to claim 1, wherein The content of TiO2 is greater than 0 mass% and less than 5.0 mass% relative to 100 mass% of the total of ZrO2, HfO2, the above-mentioned stabilizer, Nb2O5 and Ta2O5.

3. The zirconia composite sintered body according to claim 1 or 2, wherein: The content of the aforementioned Group I element is greater than 0 mol % and less than 3 mol % relative to 100 mol % of the total of ZrO 2 , HfO 2 , the aforementioned stabilizer, Nb 2 O 5 and Ta 2 O 5 .

4. The zirconia composite sintered body according to any one of claims 1 to 3, wherein The aforementioned Group I element includes at least one element selected from Li, Na and K.

5. The zirconia composite sintered body according to any one of claims 1 to 4, wherein When the content of the above-mentioned stabilizer is set to A mol % and the total content of Nb2O5 and Ta2O5 is set to B mol %, A / B is greater than or equal to 0.9 and less than or equal to 3.

6. The zirconia composite sintered body according to any one of claims 1 to 5, wherein The aforementioned stabilizer includes Y2O3 and / or CeO2.

7. The zirconia composite sintered body according to any one of claims 1 to 6, wherein The content of TiO2 is 0.6 mass% or more and 4.3 mass% or less.

8. The zirconia composite sintered body according to any one of claims 1 to 7, wherein The biaxial bending strength measured in accordance with ISO 6872:2015 is 350 MPa or more.

9. The zirconia composite sintered body according to any one of claims 1 to 8, wherein The average grain size of the aforementioned zirconium oxide composite sintered body is 0.5 to 5.0 μm.

10. The method for producing a zirconia composite sintered body according to claim 1, comprising: A step of producing a formed body using a raw material composition, wherein the raw material composition comprises ZrO2, HfO2, a stabilizer capable of suppressing phase transformation of zirconium oxide, and Nb2O5 and / or Ta2O5, In the total of 100 mol% of ZrO2, HfO2, the above stabilizer, Nb2O5 and Ta2O5, The total content of ZrO2 and HfO2 is 78-97.5 mol%. The content of the stabilizer is 1 to 12 mol%. The total content of Nb2O5 and Ta2O5 is 1 to 9 mol%. The raw material composition further comprises a raw material compound of a Group I element and TiO2; and A step of sintering the molded body.

11. The method for producing a zirconia composite sintered body according to claim 10, wherein: The raw material compound of the aforementioned Group I element is a hydroxide and / or a salt of the aforementioned Group I element, The method for producing a zirconium oxide composite sintered body further includes a step of wet-mixing the respective raw materials of the raw material composition in a solvent containing water to obtain the raw material composition.

12. The method for producing a zirconia composite sintered body according to claim 10 or 11, wherein: In the raw material composition, the stabilizer includes a stabilizer that is insoluble in ZrO 2 and HfO 2 .

13. The method for producing a zirconia composite sintered body according to any one of claims 10 to 12, wherein: The step of sintering the molded body comprises: The sintering process is performed at 1300-1680°C, and A process of performing HIP treatment at 1200°C or above.

14. The method for producing a zirconia composite sintered body according to claim 13, wherein: The method includes the step of performing a heat treatment at 1400° C. or lower in the air or in an atmosphere containing excess oxygen after performing the HIP treatment.

Citation Information

Patent Citations

  • Machinable zirconia and method for producing the same

    JP2015127294A

  • High-strength transparent zirconia sintered body, process for production thereof, and use thereof

    CN102803180A

  • High-bending-strength oral cavity repair material and preparation method thereof

    CN106693045A

  • Dental ceramics and method for the manufacture thereof

    US20070142206A1

  • Zirconia raw material, sintered zirconia compact, and cutting tool

    WO2010024171A1